2001
DOI: 10.4269/ajtmh.2001.65.76
|View full text |Cite
|
Sign up to set email alerts
|

Case report: recovery from persistent septicemic melioidosis.

Abstract: Abstract. Septicemic melioidosis is often fatal despite treatment with antibiotics such as ceftazidime to which Burkholderia pseudomallei, the causal pathogen, is sensitive in vitro. We report a near-fatal case of septicemic melioidosis with persistent B. pseudomallei bacteremia despite intravenous ceftazidime in which combination therapy with meropenem and ciprofloxacin, splenectomy and correction of metabolic acidosis allowed for hospital discharge. The choice of antibiotic agents was supported by intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…pseudomallei is susceptible to kanamycin, although this antibiotic is no longer used in the treatment of clinical melioidosis. Transposon mutation analysis has revealed that the (214). Although successful in this case, this applicability of this remains uncertain, and it is unlikely to gain widespread acceptance.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…pseudomallei is susceptible to kanamycin, although this antibiotic is no longer used in the treatment of clinical melioidosis. Transposon mutation analysis has revealed that the (214). Although successful in this case, this applicability of this remains uncertain, and it is unlikely to gain widespread acceptance.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…5 Another case of persistent septicemic melioidosis was confirmed in a patient who had visited the affected community during the outbreak, and the link with the original case cluster was made by genotyping with DNA macrorestriction analysis. 6 A second late-onset case of melioidosis was linked with the original cluster by the same method, bringing the total number of septicemic cases to seven, with three deaths and two delayed onset cases after 6 and 18 months, respectively. There were no more cases of melioidosis in the affected community and no culture-positive cases caused by the pulsotype of B. pseudomallei associated with the outbreak ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…pseudomallei strains for intracellular antibacterial susceptibility (7). Results from initial in vitro coculture studies indicated that the opacification of the growth media was due to a combination of intracellular and extracellular growth resulting from bacterium-ameba interactions (6).…”
Section: Discussionmentioning
confidence: 99%
“…At present, clinical trial data do not conclusively demonstrate an improved outcome when carbapenems are compared with ceftazidime (12), despite the theoretical benefit expected from improved intracellular penetration. In a recent case study, a previously published amebic cellular model of B. pseudomallei infection was used to demonstrate the superior intracellular activity of meropenem over ceftazidime and sulfamethoxazole (7). Although it was found that improved in vitro activity corresponded to the clinical improvement in a single persistent septicemic case, this outcome had alternative explanations based on other aspects of patient care.…”
mentioning
confidence: 99%